Silver nanoparticles affect germination and photosynthesis in tobacco seedlings - Biba, Renata (Array, 2020)
Extensive commercialization of silver nanoparticles (AgNPs) raises the risk of their accumulation in the soil-plant system. Once released into the environment, AgNPs are prone to chemical transformations, which make it hard to determine whether their phytotoxic effects are purely NP-related or a consequence of released Ag+ ions. In this study the effects of 25, 50, 75, 100 and 150 μM AgNPs and AgNO3 on seed germination and early growth of tobacco (Nicotiana tabacum L.) seedlings were compared. Additionally, the effects on photosynthetic performance and pigment content were investigated. Germination rate and index values indicated delayed and slower germination in some AgNP treatments. Lower AgNP concentrations stimulated root growth, but induced a prominent reduction in fresh weight. By contrast, all AgNO3 concentrations inhibited root growth but only the higher ones decreased fresh weight. Obtained results imply that the observed AgNP toxicity could be ascribed to NP form and can be correlated with high AgNP stability in the solid medium. On the other hand, the majority of AgNP and AgNO3 treatments induced an increase in chlorophyll content that was accompanied by significantly lower values of relative electron transport rate and coefficient of photochemical quenching, implying an inhibition of the electron transport chain. A similar impact of AgNPs and AgNO3 on photosynthesis can be correlated with lower stability of AgNPs in a liquid medium, resulting in AgNP aggregation and dissolution of Ag+ ions.